A new widespread European bee species of the genus Dasypoda Latreille (Hymenoptera, Apoidea) - Radchenko, Vladimir G. (Zootaxa, 2016)
A new bee species of the genus Dasypoda Latreille (Hymenoptera, Apoidea, Melittidae), D. morawitzi Radchenko sp. nov., is described. This species is closely related to, and easily confusable with, D. hirtipes (Fabricius), and its specimens have been previously attributed to the latter species. A comparative morphological analysis of D. morawitzi with other species of the D. hirtipes group is provided. The distribution and trophic links of this new species are discussed.